DEVELOPMENT OF STUDENTS' CREATIVE ACTIVITY THROUGH RESEARCH METHODS (World Bulletin of Education and Learning, 2026)
It is very simple and convenient to engage in the development of independent creativity of students, research and design work. On the basis of the daily use of Bunda, the need for the development of new knowledge arises.
Keywords: Project, creativity, cognitive, research, experience, knowledge, process, independent creativity, research and design.